Obese children 10 years later: an observational study - Nhingpannha-Palomba, H; Chalencon, V; Bonneterre, V; Raynaud, C; Patural, H (Archives de pédiatrie : organe officiel de la Société française de pédiatrie, 2013)
Although childhood obesity is a major public health problem, the long-term follow-up of children who are overweight and obese has rarely been studied in France. We conducted a single-center observational study of 85 subjects who received medical follow-up for weight problems or obesity in 2001, at which time they were aged between 2 and 17 years. The study followed-up these subjects in 2012, after a mean of 10 years. We separated the study into two time periods. Initial follow-up periods - (A) from the first consultation to the end of individual or group care -and latency periods - (B) from the end of medical care to the year 2012 - were distinguished. A declarative survey based on questionnaires on dietary habits, activity levels, and anthropometric data of children and their parents was conducted in 2012. Two indicators of effectiveness monitoring (α) and post-follow-up (β) were created. Although 77% of patients had a favorable α indicator, demonstrating the effectiveness of initial management, especially if it was prolonged (>32 months, P=0.007), a re-ascent of the BMI curve after ceasing monitoring occurred in half of the cases (47%) with subjects' BMI significantly correlated with their parents' BMI (P=0.004 for the mother and P=0.02 for the father). These observations encourage us to improve the medical follow-up on offer by educating and strengthening the role of parents to achieve a significant and lasting improvement in BMI and weight. In case of medical failure in supporting patients to achieve enough weight loss, the option of bariatric surgery can be considered, even if its recent introduction means that a long-term risk/benefit analysis has yet to be conducted.